FORMATION OF LAND RELATIONS OF THE UNITED TERRITORIAL COMMUNITIES OF THE REGION IN THE CONTEXT OF DECENTRALIZATION - Ivaniuk , T.L. (The actual problems of regional economy development, 2021)
The article is aimed at studying land issues, which are an important component of the development of land relations of agricultural enterprises in Ivano-Frankivsk region. It is determined that the most expedient direction of solving the problem of development of land relations of agricultural enterprises of the region are territories with favorable geographical location of OTG, in which there are economic units with land resources which include agricultural lands. The purpose of the article is to study the land relations of agricultural enterprises, namely land as its key element, in the territorial communities of Ivano-Frankivsk region. To achieve this goal, the article uses the following research methods, namely: systems analysis - to study economic processes in their interrelationship and interdependence, taking into account causation; synthesis - to summarize the disparate aspects of the study of land relations in agricultural enterprises; abstraction - to formulate generalized conclusions; graphic - to visualize the results of the study. The article identifies the main advantages and disadvantages of the formation of joint territorial; the normative-monetary assessment of agricultural lands in the regions of Ukraine is analyzed; This will make it possible to increase the revenues to the local budget of a certain territorial community in the form of land payments and taxes by enterprises. It is substantiated that in modern economic conditions of functioning of economic units land resources can become an important source of community development and help to form a powerful management mechanism in the field of land relations. The scientific novelty of the study is the grouping and analysis of agricultural enterprises and land used by them by location, connection and number in relation to the relevant territorial community of Ivano-Frankivsk region and determining the coefficient of provision of territorial communities with land resources. The results of the scientific process can be used by territorial communities and agricultural enterprises in the process of forming a program for the development of land relations.